The penguin problem - Klein, Abby; McKinley, John (New York : Scholastic, 2010)
Freddy's first grade class is learning all about penguins. When the class discovers some are endangered, they want to help. Can Freddy come up with a good plan to save the penguins?
Keywords: Endangered species -- Juvenile fiction; Humorous fiction